Advances in agaro-oligosaccharides preparation and bioactivities for revealing the structure-function relationship. (July 2021) - Jiang, Chengcheng; Cheng, Danyang; Liu, Zhen; Sun, Jianan; Mao, Xiangzhao
Graphical abstract: Highlights: The extraction methods of agar from red algae are summarized. The comparison of three methods for agaro-oligosaccharides production. The abundant bioactivities of agaro-oligosaccharides are described in detail. Agaro-oligosaccharides with different structures exhibit different bioactivities. Functional agaro-oligosaccharides play significant roles in human health. Abstract: Agaro-oligosaccharides originating from red algae have attracted increasing attention in both basic theoretical research and applied fields due to their excellent bioactivities, which indicates the wide prospects of agaro-oligosaccharides for application in the food, pharmaceutical and cosmetic industries. Thus, a considerable number of studies regarding functional agaro-oligosaccharides preparation as well as the bioactivities exploration have been carried out. Based on these studies, this review first introduced different methods that have been used in agar extraction from red algae, and further provided research progress on arylsulfatase. Then, different methods used for agaro-oligosaccharides production were summarized. Moreover, the abundant bioactivities of agaro-oligosaccharides were described in detail. Finally, this review has discussed current research problems and further provided critical aspects, which may be helpful for revealing the structure-function relationship of agaro-oligosaccharide.